Expressões sócio-espaciais da desigualdade - Ana Fani Alessandri Carlos (Confins)
This article is based on the hypothesis that the movement of capital accumulation is expressed (realized) in the space of everyday life, gaining visibility in the city, especially in metropolises such as São Paulo, through spatial differentiation. This is manifested as a product of the differentiated access of individuals and social groups to the spaces-times of the realization of life, illuminating a socio-spatial praxis. In this sense, the forms of inequality - the city as a source of deprivation - are revealed in the differentiation of spaces-times for the realization of urban practice, in the form of socio-spatial segregation.